ANALISIS UJI KINERJA PEMUTUS TENAGA (PMT) 150 KV PADA GARDU INDUK SANGGRAHAN - Faruq Ratuhaji; Nur Asmi Rahmawati; Hermansyah Hermansyah (PSRE UNIMUS, 2025)
The Circuit Breaker (PMT) is a critical component in ensuring the reliability of 150 kV transmission systems, which requires periodic testing to maintain optimal performance. This study aims to evaluate the operational feasibility of a 150 kV circuit breaker at the Sanggrahan Substation using three assessment parameters: insulation resistance, contact resistance, and synchronizing performance. The research method includes onsite testing using a 5 kV megger, RMO-600 micro-ohmmeter, and a 50 Hz Breaker Timing Analyzer, supported by interviews and literature review. The results show that the insulation resistance of all phases is significantly above the minimum standard of 0.015 GΩ, with leakage currents ranging from 0.009–0.023 mA, indicating excellent insulation conditions without signs of degradation. The measured contact resistance of 40.4–43.4 μΩ meets the requirement of being below the 50 μΩ threshold, confirming clean and stable contact performance with minimal heating potential. Furthermore, the synchronizing test demonstrates operating time differences of only 0.45 ms for opening and 0.35 ms for closing, well below the 10 ms tolerance. These findings indicate that the circuit breaker is in a highly reliable operating state and contributes positively to system reliability through reduced failure risk and improved switching performance.